2010
DOI: 10.3109/13880201003770143
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antibacterial activity of essential oils ofTripleurospermum disciformein three developmental stages

Abstract: This study demonstrates the occurrence of β-farnesene/β-sesquiphellandrene chemotype of T. disciforme in western regions of Iran that are different from previous reports. The findings also showed that the essential oils T. disciforme have excellent antibacterial activities and thus have great potentiality to be used as a resource for natural health products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 7 publications
(9 reference statements)
1
30
0
Order By: Relevance
“…Perigo et al [22] studied the chemical compositions and antibacterial activities of Piper species from distinct rainforest areas in Southeastern Brazil, and found that higher contents of β-phellandrene were positively correlated to wide spectrum antibacterial activity. Antibacterial activity of essential oils of Tripleurospermum disciforme was reported that the reason for higher antibacterial effect is the presence of β-farnesene and β-sesquiphellandrene [23]. The essential oils of Bocageopsis pleiosperma Maas rich in β-bisabolene were reported to have high antifungal activities [24].…”
Section: Resultsmentioning
confidence: 99%
“…Perigo et al [22] studied the chemical compositions and antibacterial activities of Piper species from distinct rainforest areas in Southeastern Brazil, and found that higher contents of β-phellandrene were positively correlated to wide spectrum antibacterial activity. Antibacterial activity of essential oils of Tripleurospermum disciforme was reported that the reason for higher antibacterial effect is the presence of β-farnesene and β-sesquiphellandrene [23]. The essential oils of Bocageopsis pleiosperma Maas rich in β-bisabolene were reported to have high antifungal activities [24].…”
Section: Resultsmentioning
confidence: 99%
“…β-Bisabolene has been reported to exhibit the potential to restore the effectiveness of ampicillin against resistant S. aureus [15]. Likewise, some studies demonstrated that Germacrene D, (Z,E)-α-Farnesene and β-Caryophyllene have significant antibacterial and antifungal activities [16][17][18]. Antioxidant activity test: A single assay does not accurately account for all of the groups of antioxidant compounds, particularly in a complex system.…”
Section: Antibacterial Activity Testmentioning
confidence: 99%
“…It is odoriferous, and terpene-like substances occur in other natural sources: the trail markers of red fire ants (Van der Meer et al, 1982), alarm pheromones of aphids (Sun et al, 2012), and even a defense substance of wild potato plants against aphids (Bruce et al, 2005). The limited number of recent investigations has revealed that FNS possesses a wide range of important biological activities such as antibacterial activity (Chehregani et al, 2010), antifungal activity (Al-Maskri et al, 2011), and free radical-scavenging activity (Sarikurkcu et al, 2013). Furthermore, a recent study showed that FNS possesses anticarcinogenic activity (Afoulous et al, 2013).…”
Section: Introductionmentioning
confidence: 99%